2011
DOI: 10.1061/(asce)nh.1527-6996.0000037
|View full text |Cite
|
Sign up to set email alerts
|

Is It Time to Go Yet? Understanding Household Hurricane Evacuation Decisions from a Dynamic Perspective

Abstract: To better understand household hurricane evacuation decisions, this paper addresses a limitation to existing hurricane evacuation modeling aspects by developing a dynamic model of hurricane evacuation behavior. A household's evacuation decision is framed as an optimal stopping problem where every potential evacuation time period prior to the actual hurricane landfall, the household's optimal choice is to either evacuate, or to wait one more time period for a revised hurricane forecast. We build a realistic mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(16 citation statements)
references
References 15 publications
1
15
0
Order By: Relevance
“…The evacuation costs also vary with different categories of hurricanes, and the costs associated with major hurricanes are much higher compared to that of minor hurricanes. Czajkowski (2011) also estimated the expected costs of not evacuating and found that the expected costs of not evacuating are substantially higher than the expected costs of evacuating. This implies the social benefits and crucial needs of efficient organization of evacuation activities.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…The evacuation costs also vary with different categories of hurricanes, and the costs associated with major hurricanes are much higher compared to that of minor hurricanes. Czajkowski (2011) also estimated the expected costs of not evacuating and found that the expected costs of not evacuating are substantially higher than the expected costs of evacuating. This implies the social benefits and crucial needs of efficient organization of evacuation activities.…”
Section: Introductionmentioning
confidence: 98%
“…Estimated costs (including lodging, meals, entertainment and travel time) varied from $211 to $292 for different storm categories. Czajkowski (2011) looked into the timing of evacuation before a hurricane landfall and showed that over time the cost of evacuation substantially changes; it initially increases, reaches to a peak and then decreases. The evacuation costs also vary with different categories of hurricanes, and the costs associated with major hurricanes are much higher compared to that of minor hurricanes.…”
Section: Introductionmentioning
confidence: 99%
“…The types of information available to local officials are well understood; the National Hurricane Center (NHC) and regional Weather Forecast Offices (WFOs) provide information about a hurricane's current status-including location, intensity (Saffir-Simpson category), and size (radius of tropical storm wind)-and likely future behavior (e.g., forecast track, uncertainty cone, storm surge, and rainfall). Unfortunately, it is unclear how local officials integrate this information about storm behavior with their counties' evacuation time estimates (ETEs) in order to decide whether and when to issue evacuation orders (Baker 2000;Lindell 2008Lindell , 2013; Murray-Tuite and Wolshon 2013)-a process that can be modeled as a dynamic decision in which the long periods of forewarning for most hurricanes allow decision makers to periodically update their threat perceptions and their PARs (Czajkowski 2011). Specifically, local officials should initiate evacuations everyplace that is likely to be affected by wind, storm surge, and inland flooding of that storm's intensity (i.e., the hurricane risk area).…”
Section: Introductionmentioning
confidence: 99%
“…Some articles that present evacuation models are those by Chiu and Zheng [29], Czajkowski [36], Li et al [71], Liu et al [75], and Ozdamar [88]. As an example, Ozdamar [ Evidently, health-related activities are also fundamental in the response stage (Liu et al [75], Valdmanis et al [114]).…”
Section: Responsementioning
confidence: 96%